Evaluate the following expression:
n → ∞ lim ( n 2 1 + n 2 2 + . . . + n 2 n − 1 ) = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The sum of the numerators should be n^2/2
I submitted my ans 2 in place of 1/2 in a hurry, oopppssss!!!
an alternate method is to recognize this is a Riemann sum, i.e n → ∞ lim n 1 k = 1 ∑ n − 1 n k = ∫ 0 1 x dx = 2 1
That is the easiest one
As the common denominator n 2 , We can add all the numbers from 1 to n − 1 in the numerator simply arithmetic sum formula : S = 2 ( 1 + ( n − 1 ) ) ⋅ n )
S = 2 n 2
l i m x → ∞ n 2 S = l i m x → ∞ n 2 2 n 2
Cancel out n 2
l i m x → ∞ 2 1 = 2 1
Simply, the sum above the line of the fraction is the sum of the first n-1 natural numbers. After the reduction, dividing by n, both parts of the ratio, we come to the result of 1/2.
Can we use the Stolz -Cesaro theorem?
= n → ∞ lim ( n 2 1 + n 2 2 + ⋯ + n 2 n − 1 ) = n → ∞ lim n 2 1 + 2 + ⋯ + n − 1 = n → ∞ lim n 2 1 2 ( n − 1 ) ( n − 2 ) = n → ∞ lim 2 n 2 n 2 − 3 n + 2 = n → ∞ lim 2 1 − n 3 + n 2 2 = 2 1 − 0 + 0 = 2 1
Problem Loading...
Note Loading...
Set Loading...
L = n → ∞ lim ( n 2 1 + n 2 2 + n 2 3 + ⋯ + n 2 n − 1 ) = n → ∞ lim n 2 1 k = 1 ∑ n − 1 k = n → ∞ lim n 2 1 × 2 ( n − 1 ) n = n → ∞ lim 2 n 2 n 2 − n = n → ∞ lim 2 1 − n 1 = 2 1 = 0 . 5 Divide up and down by n 2